(untitled) (Hilo Analítico, 2023)
The problems in the social skills and mental health of deaf people in Colombia are increasing every day, which has led to identifying the incidents that are occurring in their communication, social interaction and teamwork, so that, according to the results and recommendations, raise awareness about the importance of inclusion in higher education for deaf people, aiming to improve their physical, emotional and mental well-being. Therefore, the present research aims to analyze the current state of research on the implementation of Colombian Sign Language in higher education as an inclusion strategy and the impact on the social skills of non-hearing people throughout the century XXI. From a documentary review, with a quantitative approach, descriptive scope and empirical-analytical epistemological. A total of 39 negative incidents were found in the communication skills of deaf people and 11 with positive incidences. In interaction skills, 44 investigations with negative incidences and 9 with positive incidences were found. For teamwork skills, 38 publications with negative incidences and 5 with positive incidences. The city of Bogotá is the one that refers the most research on the social skills of deaf people who use the Colombian sign language in the last century, according to the results obtained.